THE EFFECTIVENESS OF USING MONOPOLY GAME TO TEACH VOCABULARY AT SMP NAHDLATUTH THALABAH - Windyasih, Vrischa Ayu; Fajarina, Maskhurin (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2023)
This research was conducted to overcome the problems faced by students in learning English, especially in learning vocabulary mastery in class VIID of SMP Nahdlatuth Thalabah. Applying monopoly games as learning media is one solution to overcome these problems. Using monopoly games in learning can make the atmosphere in the classroom livelier, so that students are more interested in learning vocabulary mastery. The objectives of the study are to find out: 1) The students’ vocabulary mastery before using monopoly game. 2) The students’ vocabulary mastery after using monopoly game. 3) The difference of students’ vocabulary mastery between before and after being given treatment using monopoly game. This study uses a quantitative approach with the type of research Pre-Experimental Design. The instrument used in this study was a test consisting of a pretest and posttest. The result of this research is that monopoly game is effectively used in learning vocabulary mastery. This effectiveness can be known through the results of student scores. In the pretest, the average value of class VIID students was 47.50. After being treated using a monopoly game, the average posttest score of class VIID students was 58.50. Based on the Paired Sample T Test, it is known that the value of Sig. (2 tailed) of 0.000 <0.05, then H0 is rejected and Ha is accepted. So it can be concluded that there is a significant difference between vocabulary mastery in the pretest and posttest data of Class VIID students at SMP Nahdlatuth Thalabah.